A Poetry Coffee House: Creating a Cool Community of Writers. (19th June 2017) - Ferguson, Kristen
Abstract: This article explores the sharing of writing through a coffee house–style poetry reading. Although this article focuses on a workshop and share activity used in a preservice teacher language arts and literacy course, it contains tips and ideas for implementing poetry coffee houses with elementary and secondary school students and preservice and inservice teachers. The coffee house activity with preservice teachers consists of three parts: a discussion about poetry, a poetry writing workshop, and an open mike sharing session. The goals of the coffee house are to broaden preservice teachers' conceptions of poetry, to model poetry writing with students, and to create a venue to share poetry as a community of writers.